On the Digital Psychopharmacology of Valproic Acid in Mice - Bass, John Samuel; Tuo, Anney H.; Ton, Linh T.; Jankovic, Miranda J.; Kapadia, Paarth K.; Schirmer, Catharina; Krishnan, Vaishnav (Frontiers in Neuroscience, 2020)
Antiepileptic drugs (AEDs) require daily ingestion for maximal seizure prophylaxis. Adverse psychiatric consequences of AEDs present as: (i) reversible changes in mood, anxiety, anger and/or irritability that often necessitate drug discontinuation, and (ii) autism and/or cognitive/psychomotor delays following fetal exposure. Technical advances in quantifying naturalistic rodent behaviors may provide sensitive preclinical estimates of AED psychiatric tolerability and neuropsychiatric teratogenicity. In this study, we applied instrumented home-cage monitoring to assess how valproic acid (VPA, dissolved in sweetened drinking water) alters home-cage behavior in adult C57BL/6J mice and in the adult offspring of VPA-exposed breeder pairs. Through a pup open field assay, we also examined how prenatal VPA exposure impacts early spontaneous exploratory behavior. At 500-600mg/kg/d, chronic VPA produced hyperphagia and increased wheel-running without impacting sleep, activity and measures of risk aversion. When applied to breeder pairs of mice throughout gestation, VPA prolonged the latency to viable litters without affecting litter size. Two-week old VPA-exposed pups displayed open field hypoactivity without alterations in thigmotaxis. As adults, prenatal VPA-exposed mice displayed active state fragmentation, hypophagia and increased wheel running, together with subtle alterations in home-cage dyadic behavior. Together, these data illustrate how automated home-cage assessments of spontaneous behavior capture an ethologically centered psychopharmacological profile of enterally administered VPA that is aligned with human clinical experience. By characterizing the effects of pangestational VPA exposure, we discover novel murine expressions of pervasive neurodevelopment. Incorporating such rigorous assessments of psychological tolerability may inform the design of future AEDs with improved neuropsychiatric safety profiles, both for patients and their offspring.